Internalisasi Ajaran Catur Paramitha dalam Pembelajaran Pendidikan Agama Hindu Sebagai Upaya Pembentukan Karakter Generasi Muda Hindu - Prianata, Eko; Sendyani, Putu Niti Darma; Jaya Kusuma, Ketut Anggra; Sumartana, I Putu; Rantauwan, Ketut Deni (Samsara Institute Publisher, 2025)
This study aims to analyze the internalization of Catur Paramitha teachings in Hindu Religious Education as an effort to shape the character of young Hindu students. Catur Paramitha, consisting of Maitri (loving-kindness), Karuna (compassion), Mudita (sympathetic joy), and Upeksa (equanimity and emotional balance), serves as an ethical guideline to foster religiosity, empathy, discipline, and inner peace among students. This qualitative study employs a case study approach through classroom observation, interviews, and document analysis. The results indicate that the role of teachers as role models and facilitators, supported by interactive lectures, group discussions, and project-based learning, effectively instills the values of Catur Paramitha. Student involvement in religious, social, and community activities further strengthens the internalization of these virtuous values. The study concludes that the internalization of Catur Paramitha can develop young Hindu students who are morally upright, responsible, religious, and harmonious in their relationship with God, fellow humans, and nature.